2003
DOI: 10.1016/s0195-668x(03)00003-4
|View full text |Cite
|
Sign up to set email alerts
|

Bupropion SR for smoking cessation in smokers with cardiovascular disease: a multicentre, randomised study

Abstract: After 7 weeks of bupropion SR treatment, more than twice as many smokers with CVD had quit smoking at 1 year compared with placebo. The safety profile of bupropion SR was similar to that previously observed in general smoking populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
1
10

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(113 citation statements)
references
References 20 publications
3
99
1
10
Order By: Relevance
“…In Smokeless group it was 28.1% at week 6, 8 and 12 in pharmacotherapy group and 50%, 53.8% and 53.8% respectively in combined therapy group while in smokers abstinence rate at 6, 8 and 12 week was 16.7%, 33.3% and 33.3% respectively in pharmacotherapy group and 45.5%, 54.5% and 54.5% in combined therapy group. We found varied result in other studies like study by Tonstad et al (2003) of 629 subjects, it has been found that the continuous abstinence rates from week 4 to 26 and 4 to 52 continued to be more than double for bupropion SR compared with placebo (27 vs 11%; 22 vs 9%). Another randomized, placebo-controlled trial of 509 smokers, Aubin et al (2004) revealed that the continuous abstinence rates in bupropion group and placebo group were 41% and 21% for week 4 to 7, and 25% and 13% for weeks 4 to 26, respectively.…”
Section: Discussioncontrasting
confidence: 58%
“…In Smokeless group it was 28.1% at week 6, 8 and 12 in pharmacotherapy group and 50%, 53.8% and 53.8% respectively in combined therapy group while in smokers abstinence rate at 6, 8 and 12 week was 16.7%, 33.3% and 33.3% respectively in pharmacotherapy group and 45.5%, 54.5% and 54.5% in combined therapy group. We found varied result in other studies like study by Tonstad et al (2003) of 629 subjects, it has been found that the continuous abstinence rates from week 4 to 26 and 4 to 52 continued to be more than double for bupropion SR compared with placebo (27 vs 11%; 22 vs 9%). Another randomized, placebo-controlled trial of 509 smokers, Aubin et al (2004) revealed that the continuous abstinence rates in bupropion group and placebo group were 41% and 21% for week 4 to 7, and 25% and 13% for weeks 4 to 26, respectively.…”
Section: Discussioncontrasting
confidence: 58%
“…Tonstada ve ark. 'nın 28 merkezi kapsayan ve kardiyovasküler hastalığı olan 629 hastayı kapsayan çalışmalarında, bir yılın sonunda bupropion kullanan grupta plaseboya göre bırakma oranı açısından iki kat fark saptanmıştır (39) . Bupropion ile yapılan çalışmalarda plasebo ile karşılaştırıldığında kardiyovasküler yan etki riskinde artış izlenmemiş-tir (40)(41)(42)(43) .…”
Section: Kardiyovasküler Hastalıklarunclassified
“…smoking abstinence rates were reported to be 34%, 27%, and 22% at 3-, 6-and 12-month follow-up as compared with 15%, 11%, and 9%, respectively, with placebo treatment. 7 trials suggest up to 30% 1-year cessation rates with a dose-related response. 8 the clinical utility of nrt assessed in a Cochrane review 9 demonstrated that all of the commercially available forms of nrt were shown to increase the odds of successfully stopping cigarette smoking by 50-70%.…”
Section: Diabetes Managementmentioning
confidence: 99%